About the motions close to synchronous ones of a charged particle in an electromagnetic wave - Nikitina, N.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The conditions of existence of the motions close to synchronous ones of a charged particle in an electromagnetic wave are presented. The effect of formation of a cluster of the ionized plasma is considered.